2020
DOI: 10.3390/molecules25235627
|View full text |Cite
|
Sign up to set email alerts
|

Content of Phenolic Compounds and Organic Acids in the Flowers of Selected Tulipa gesneriana Cultivars

Abstract: The study focused on the determination of phenolic acids, flavonoids and organic acids in five tulip cultivars ‘Barcelona’, ‘Columbus’, ‘Strong Gold’, ‘Super Parrot’ and ‘Tropicana’. The cultivars grown in field and in a greenhouse were exposed after cutting to different times of storage (0, 3 and 6 days). The phenolic profile contained 4-hydroxybenzoic, 2,5-dihydroxybenzoic, gallic, vanillic, syringic, salicylic, protocatechuic, trans-cinnamic, p-coumaric, caffeic, ferulic, chlorogenic and sinapic acids, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…Many organic acid compounds are mainly classified into small molecule phenolic acid compounds and acylated organic acid compounds according to their structure ( Krzymińska et al, 2020 ). A total of 18 organic acid and amino acid chemical components (compound 1-6, 8-10, 12, 18-19, 21, 23, 25, 31-32, and 70) were identified in this study: quinic acid, malic acid, arginine, proline, tyrosine, citric acid, isoleucine, 3,4-dihydroxybenzaldehyde, phenylalanine, danshensu, 3-indoleacrylic acid, tryptophan, 3,5-dimethoxy-4-hydroxycinnamic acid, gentisic acid, chlorogenic acid, 4-ocaffeoylquinic acid, ferulic acid, and isochlorogenic acid.…”
Section: Resultsmentioning
confidence: 99%
“…Many organic acid compounds are mainly classified into small molecule phenolic acid compounds and acylated organic acid compounds according to their structure ( Krzymińska et al, 2020 ). A total of 18 organic acid and amino acid chemical components (compound 1-6, 8-10, 12, 18-19, 21, 23, 25, 31-32, and 70) were identified in this study: quinic acid, malic acid, arginine, proline, tyrosine, citric acid, isoleucine, 3,4-dihydroxybenzaldehyde, phenylalanine, danshensu, 3-indoleacrylic acid, tryptophan, 3,5-dimethoxy-4-hydroxycinnamic acid, gentisic acid, chlorogenic acid, 4-ocaffeoylquinic acid, ferulic acid, and isochlorogenic acid.…”
Section: Resultsmentioning
confidence: 99%
“…[48] Four phenolic acids (gallic acid-1.05 ± 0.61 (mg/g); caffeic acid-0.19 ± 0.02 (mg/g); ferulic acid-0.48 ± 0.27 (mg/g); rosmarinic acid-5.49 ± 0.96 (mg/g)) were also identified in the flower extract of Lavandula angustifolia Mill., by ultrasound-assisted extraction with natural eutectic solvents (NADESs) and reference solvents (70% ethanol, 80% methanol) [48]. Krzymi ńska et al [49], studied the phenolic acid profile of five cultivars of Tulipa gesneriana L., in which significant amounts of hydroxybenzoic acids (phydroxybenzoic, 2,5-dihydroxybenzoic, gallic, vanillic, syringic, salicylic, protocatechuic), and hydroxycinnamic acids (trans-cinnamic, p-coumaric, caffeic, ferulic, chlorogenic, sinapic) were identified, while it was noted that the profile of the phenolic acids of the flowers studied varied according to the cultivar, the production system, and the storage time.…”
Section: Taraxacum Campylodesmentioning
confidence: 99%
“…The flowers of buckwheat (Fagopyrum Esculentum Moench) also contain the highest amounts of catechin compared to other plant parts, while Cucurbita pepo L. [102] and highbush blueberry (Vaccinium angustifolium L. [105]) flowers are also a good source of (+)-catechin and (−)-epicatechin. Krzymi ńska et al [49] reported a varied content of catechins in various Tulipa gesneriana cultivars under different cultivation systems. In the recent study by de Morais et al [106], the edible flowers of eight species with different colors (mini rose (Rosa chinensis Jacq.…”
Section: Flavanolsmentioning
confidence: 99%
“…Flowers are involved in sexual reproduction, secreting attractive and/or rewarding chemicals to animal pollinators such as proline and GABA (Biancucci et al, 2015; Sosenski & Parra‐Tabla, 2019). Several bioactive antioxidant polyphenols, carotenoids, anthocyanins, organic acids, terpenes, alkaloids, and saponins, which can modulate multiple CNS neurotransmitter pathways, are high storage in petals and other parts of flowers (Chen et al, 2018; da Fonseca et al, 2020; Krzymińska et al, 2020; Kumari et al, 2021). Currently, in anxiety drug development, the multitarget approach is a novel rational strategy supported by the implication of disturbances in multiple complex neuronal systems (Sartori & Singewald, 2019).…”
Section: Introductionmentioning
confidence: 99%